MICROPROPAGATION ET RHIZOGENESE IN VITRO CHEZ NAUCLEA LATIFOLIA SMITH (RUBIACEAE) - Rassimwaï Pitekelabou; Kodjo Djidjolé Etse; Atsou Vincent Aïdam (European Scientific Journal, ESJ, 2013)
To contribute to environmental protection and to reduce the rarefaction of the Nauclea latifolia, micropropagation and production of roots in vitro were undertaken. In this work, the young seedlings used were obtained from in vitro germination of seeds. Two culture media, MS and WPM, gave identical results. Benzylaminopurine (BAP) induces shoots proliferation and Indol-butyric acid (IBA) promotes roots proliferation. Activated charcoal inhibits the rhizogenesis. IBA 19,68 μM induces cal formation from foliar fragments. Callus obtained with Naphtalen-acetic acid (NAA) 2,68 -5,37 – 10,74 and 21,48 μM initiate roots.